2000
DOI: 10.1002/(sici)1097-4695(200004)43:1<1::aid-neu1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific effects of bone morphogenetic proteins on the oligodendrocyte lineage

Abstract: Oligodendrocyte maturation is regulated by multiple secreted factors present in the brain during critical stages of development. Whereas most of these factors promote oligodendrocyte proliferation and survival, members of the bone morphogenetic protein family (BMPs) recently have been shown to inhibit oligodendrocyte differentiation in vitro. Oligodendrocyte precursors treated with BMPs differentiate to the astrocyte lineage. Given that cells at various stages of the oligodendrocyte lineage have distinct respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 63 publications
8
82
2
Order By: Relevance
“…Moreover, cell-extrinsic signaling molecules (e.g., neurotrophin-3 [NT-3] and fibroblast growth factor-2 [FGF-2]) that enhance the self-renewal of progenitors dividing in response to PDGF cause cells to become more reduced. In contrast, signaling molecules that induce differentiation to oligodendrocytes (i.e., thyroid hormone [TH] [63,64]) or astrocytes (i.e., bone morphogenetic protein-4 [BMP-4] [65,66]) cause cells to become more oxidized [59]. The ability of these signaling molecules to alter redox state is essential to their mechanisms of action, because pharmacological inhibition of the redox changes they induce blocks their effects on either division or differentiation of O-2A/OPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cell-extrinsic signaling molecules (e.g., neurotrophin-3 [NT-3] and fibroblast growth factor-2 [FGF-2]) that enhance the self-renewal of progenitors dividing in response to PDGF cause cells to become more reduced. In contrast, signaling molecules that induce differentiation to oligodendrocytes (i.e., thyroid hormone [TH] [63,64]) or astrocytes (i.e., bone morphogenetic protein-4 [BMP-4] [65,66]) cause cells to become more oxidized [59]. The ability of these signaling molecules to alter redox state is essential to their mechanisms of action, because pharmacological inhibition of the redox changes they induce blocks their effects on either division or differentiation of O-2A/OPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Among key pathways implicated in GFAP regulation, CNTF/LIF/CT-1 cytokine signaling through gp130 and JAK/STAT has been shown in several developmental models to be a key regulator of GFAP and astrocyte differentiation as a whole (Barnabe-Heider et al, 2005; Bonni et al, 1997; Miller and Gauthier, 2007; Sun et al, 2001). Additionally, Notch- and BMP-signaling have been implicated in regulating GFAP-expression and some aspects of astrocyte development, including inhibition of alternative cell fates (Bonaguidi et al, 2005; Grinspan et al, 2000; Namihira et al, 2009; Taylor et al, 2007). Newborn neurons are thought to be the source of these signaling molecules, as separate studies have suggested that CT-1 and Jagged/delta released from neurons promote astrocyte differentiation in vitro (Barnabe-Heider et al, 2005; Namihira et al, 2009).…”
Section: Astrocyte Developmentmentioning
confidence: 99%
“…OPC and oligodendrocytes derived from the CNS show expression of BMP4 and BMP receptors [171]. Exogenous BMP4 inhibits OPC differentiation and promotes astroglial differentiation [172,173]. Recently, it has been shown that BMP signaling is active in demyelinating lesions in mice [174].…”
Section: Bone Morphogenetic Proteinmentioning
confidence: 99%